FAMILY NURSING CARE IN FAMILY WITH DIABETES MELLITUS WITH A FOCUS OF INAFFECTIVENESS MANAGEMENT OF TYPE 2 DIABETES MELLITUS DIET IN BANJARNEGARA DISTRICT - Danik Rakhmawati; Muhammad Iqbal Ramadlan; Moh Ridwan (Jurnal Keperawatan Respati Yogyakarta, 2022)
Diabetes is something that cannot be explained with clear and concise answers, but in general it can be described as a series of anatomical and chemical problems caused by various factors. Data from the World Health Organization (2015) shows that Indonesia has the seventh highest number of people with diabetes in the world, after China, India and the United States, with a population of 230 million in 2015 which reached 5.8% or around 8.5 million people suffer from diabetes. diabetes. The purpose of this study aims to obtain an overview in treating clients with diabetes mellitus with the problem of ineffectiveness of diet management of type 2 diabetes mellitus. The method of writing this case study uses descriptive analysis, is a nursing process method that focuses on one of the most important issues in each case, namely patient care. Diabetes, focuses on the ineffectiveness of the diet for type 2 diabetes. From the results and discussion that the client named Mr. S the reason the client was studied was to determine the client's dietary compliance. When the assessment is carried out, the client suffers from DM who has entered stage V with a developmental stage that has not been passed, namely stages VI to VIII. From the results of nursing care carried out, the problem of adherence to the Diabetes Mellitus diet was partially resolved. When the assessment is carried out, the client suffers from DM who has entered stage V with a developmental stage that has not been passed, namely stages VI to VIII. From the results of nursing care carried out, the problem of adherence to the Diabetes Mellitus diet was partially resolved. When the assessment is carried out, the client suffers from DM who has entered stage V with a developmental stage that has not been passed, namely stages VI to VIII. From the results of nursing care carried out, the problem of adherence to the Diabetes Mellitus diet was partially resolved.